Challenges And Prospects Of National Legal Reform In Promoting The Digitalization Of Coal Mining Through Artificial Intelligence - Badrunsyah, Badrunsyah (Green Publisher Indonesia, 2025)
The digitalization of the coal mining sector through the adoption of Artificial Intelligence (AI) technology represents a strategic step toward enhancing efficiency, transparency, and sustainability in the extractive industry. However, the implementation of AI in this sector still faces complex legal challenges, including regulatory gaps, weak institutional coordination, and the absence of national technical standards. This study aims to examine the challenges and prospects of national legal reform in supporting the digital transformation of coal mining through a normative juridical approach. The method employed is library research with descriptive qualitative analysis and comparative studies of regulations in other countries such as Australia and Canada. The findings indicate the necessity for regulatory revision, the establishment of AI standards, and multi-stakeholder collaboration as key factors for the success of national legal reform in the mining digitalization era. This study recommends accelerating the formulation of AI regulations in the mining sector as part of the national digital transformation strategy.